Elastoplastic model for discontinuous shear deformation of deep rock mass - Wang, Ming-yang; Fan, Peng-xian; Qian, Qi-hu; Deng, Hong-jian (Journal of Central South University, 2011)
Deep rock mass possesses some unusual properties due to high earth stress, which further result in new problems that have not been well understood and explained up to date. In order to investigate the deformation mechanism, the complete deformation process of deep rock mass, with a great emphasis on local shear deformation stage, was analyzed in detail. The quasi continuous shear deformation of the deep rock mass is described by a combination of smooth functions: the averaged distribution of the original deformation field, and the local discontinuities along the slip lines. Hence, an elasto-plastic model is established for the shear deformation process, in which the rotational displacement is taken into account as well as the translational component. Numerical analysis method was developed for case study. Deformation process of a tunnel under high earth stress was investigated for verification.